ChemInform Abstract: One‐Pot Two‐Step Synthesis of 1‐Position Arylated 1, 3‐Disubstituted Isoquinoline N‐Oxides. Issue 11 (8th March 2013) - Ding, Qiuping; Wang, Dan; Sang, Xiaoyan; Lin, Yuqing; Peng, Yiyuan
Abstract The transformation involves an in situ generation of isoquinoline N‐oxides which is followed by a Pd‐mediated direct arylation.